Development of a Prototype-Based Scale for Assessing Saudade. (December 2020) - Neto, Félix; Mullet, Etienne
Saudade is a psychological experience resulting from the absence of significant others or familiar places. Four studies were conducted in view of creating a measure of saudade derived from previous prototype analyses. Data from four samples were collected: two samples of Portuguese undergraduate students, one sample of Portuguese adults, and one sample of Portuguese adolescents. Through exploratory and confirmatory factor analyses, a three-factor latent structure of saudade was identified: Missing Close Others, Lack of Intimacy, and Longing for the Past . This three-factor structure was meaningfully associated with theoretically related constructs such as life satisfaction, negative affect, loneliness, love satisfaction, self-esteem, or neuroticism and was not associated with theoretically unrelated constructs such as tolerance or openness.